PENGEMBANGAN BAHAN AJAR BAHASA INDONESIA KELAS IV DI SEKOLAH DASAR DENGAN PENDEKATAN SAINTIFIK - Aminarti Aminarti (MEDIA DIDAKTIKA, 2015)
The research was aimed to (1) find the problems and needs of the teachers and students of elementary school, planning, prototype teaching materials Bahasa Indonesia subject lesson and (2) describe responses to the acceptability of the stake holders to Bahasa Indonesia teaching materials using scientific approach in the first state elementary school of Paciran.The type of the research was a study by the method of model development (design) or conceptual development with 6 steps, Procedure development included: (1) planning (2) exploratory study (3) development of an early form of the product. Techniques of the data collection by (1) interview, (2) observation; (3) (FGD);analysis was done qualitatively and quantitatively.Teaching materials appreciation prose fiction that was developed by researcher with the scientific approach felt/ believed to be very suitable for elementary school students products Indonesian teaching materials with scientific approach; through a three-step validation has developed the initial product Indonesian teaching materials that have proven validity and effectiveness through t-test Independent and Non - Independent, three development steps were: (a) expert judgment; (b) the initial development and refinement; (c) a major development in the field and repair. The stakeholders gave a good appreciation the teaching material of Bahasa Indonesia subject lesson which used scientific approach, statistical tests showed that the teaching materials produced was effective for learning Bahasa Indonesia subject lesson at elementary school.